Analysis of Factors Influencing Risk Management of Non-financial Companies Listed on the IDX - Nurjaman; Abdul Fatah Hassanudin; Agus Rahmadsyah; Amir Hakim (Outline Publisher, 2023)
Risk management is the company's efforts to manage various risks that occur. Risk Management is very important for companies in managing and avoiding company risks. This study aims to analyze the factors that influence risk management in companies. Several factors that affect risk management are Profitability, Leverage, Company Size, Industry Type, and Business Complexity. This research was conducted on non-financial companies on the Indonesian Stock Exchange. The sample collection method used is purposive sampling in which the research sample is included in the predetermined criteria. This study uses a quantitative method with multiple linear regression analysis. The results of the study show that the factors that influence risk management, namely Profitability, Leverage, Company Size, Industry Type, and Business Complexity, have an effect on company Risk Management. It is important for companies to pay attention to and manage their risk management as a step to control and minimize the risks that exist in the company.